The EFFECT OF HONEY THERAPY ON THE GRADE OF GANGRENIC WOUNDS IN TYPE 2 DIABETES MELLITUS PATIENTS: PENGARUH TERAPI MADU TERHADAP GRADE LUKA GANGREN PADA PASIEN DIABETES MELITUS TIPE 2 - Susanti, Novia; Udiyani, Ritna; Hasanah, Noor (WELL BEING, 2025)
Diabetic foot ulcers are often associated with infection events that cause wounds to become wider, leading to ulcers and gangrene. Therefore, one of the treatments using honey therapy can help the wound healing process. The purpose of this study was to determine the effect of honey therapy on the grade of gangrene wounds in patients with type 2 diabetes mellitus. The design in this study employed a pre-experimental design with a one-group pretest and posttest. The sample in this study amounted to 10 people using purposive sampling techniques, instruments using observation sheets, and analysis methods with the Wilcoxon Test. The results of the study showed that before being given honey therapy, it was known that almost all (60%) were included in the category of grade III foot ulcers, and after being given honey therapy, most (60%) experienced a decrease to grade II. The results of the statistical test obtained a p-value of 0.002 (<0.005) which means that there is an effect of honey therapy on diabetic foot ulcers in patients with type 2 diabetes mellitus. It is recommended for health workers such as home care nurses and medical teams to be able to provide education to patients with type 2 diabetes mellitus foot ulcers about the benefits of honey in healing diabetic foot ulcers.